Relations between symptom severity, illness perceptions, visceral sensitivity, coping strategies and well-being in irritable bowel syndrome guided by the common sense model of illness. Issue 5 (28th May 2017) - Knowles, Simon R.; Austin, David W.; Sivanesan, Suresh; Tye-Din, Jason; Leung, Chris; Wilson, Jarrad; Castle, David; Kamm, Michael A.; Macrae, Finlay; Hebbard, Geoff
Abstract: Irritable Bowel Syndrome (IBS) is a common condition affecting around 10–20% of the population and associated with poorer psychological well-being and quality of life. The aim of the current study was to explore the efficacy of the Common Sense Model (CSM) using Structural Equation Modelling (SEM) in an IBS cohort. One hundred and thirty-one IBS patients (29 males, 102 females, mean age 38 years) participating in the IBSclinic.org.au pre-intervention assessment were included. Measures included IBS severity (Irritable Bowel Syndrome Severity Scoring System), coping patterns (Carver Brief COPE), visceral sensitivity (Visceral Sensitivity Index), illness perceptions (Brief Illness Perceptions Questionnaire), psychological distress (Depression, Anxiety and Stress Scale), and quality of life (IBS Quality of Life scale; IBS-QoL). Using SEM, a final model with an excellent fit was identified ( χ 2 (8) = 11.91, p  = .16, χ 2 / N  = 1.49, CFI > .98, TLI > .96, SRMR < .05). Consistent with the CSM, Illness perceptions were significantly and directly influenced by IBS severity ( β  = .90, p  < .001). Illness perceptions in turn directly influenced maladaptive coping ( β  = .40, p  < .001) and visceral sensitivity ( β  = .70, p  < .001). Maladaptive coping and visceral sensitivity were significantly associated with psychological distress ( β  = .55, p  < .001; β  = .22, p  < .01) and IBS-QoL ( β  = –.28, p  < .001; β  = –.62, p  < .001). Based on these findings, we argue that to augment the adverse impact of IBS severity on IBS-QoL and psychological distress, psychological interventions will be best to target the mediating psychological processes including illness beliefs, visceral sensitivity and maladaptive coping.